Evaluation of electrical properties of glass-ceramics obtained from mill scale. (December 2015) - Montedo, O.R.K.; Alves, I.T.; Faller, C.A.; Bertan, F.M.; Piva, D.H.; Piva, R.H.
Graphical abstract: Impedance spectra: (a) G2Z and (b) G1Z. The graphs (c) and (d) represent the imaginary part of the impedance as a function of the logarithm of the frequency for samples G2Z and G1Z, respectively. Highlights: We produced glass-ceramics from mill scale and evaluated electrical properties. Physical hindrance of the Na + ions with the addition of ZrO2 reduced conductivity. Higher resistivity values for these glass-ceramics were obtained at T  < 950 °C. Dielectric constant values ranged from 41 to 104 at 300 °C. These glass-ceramics are potential low cost materials for LTCC application. Abstract: The inertization of hazardous chemical elements has been shown to be an efficient way to achieve the waste valorization (e.g., mill scale) generated during the steel production process. Vitrification is an inertization technique which is used to obtain glass-ceramic materials with notable characteristics, such as electrical properties. In this context, this study aims to evaluate electrical characteristics of glass-ceramic materials produced from mill scale by means of impedance spectroscopy. Six compositions were prepared by melting and powder technology in order to obtain glass-ceramics. Electrochemical impedance spectroscopy measurements showed that the electrical conductivity of the glass-ceramics was strongly dependent on the structural modifications, particularly when these affect the Na + charge carrier. Crystallization reduced the electrical conductivity due to the physical hindrance of the Na + ions with the addition of ZrO2 . Moreover, higher resistivity values for these glass-ceramics (up to 2.5 × 10 4  Ω m) were obtained at temperatures below 950 °C when the electrical conductivity was as low as 10 −10  S m −1 . At 300 °C, ϵ values ranged from 41 to 104. The relative ease with which the electrical properties can be changed makes these glass-ceramics potential low cost materials for application as glass semiconductors in thermal insulation or as LTCCs for microelectronic devices.